An Ulcerated Ileal Gastrointestinal Stromal Tumor Disguised as Acute Appendicitis - Ashish Lal Shrestha; Girishma Shrestha (Case Reports in Surgery)
Background. Gastrointestinal stromal tumor (GIST) of the ileum is not a common differential to consider in the management of acute right iliac fossa (RIF) pain and tenderness. Finding of a normal-looking appendix intraoperatively should arouse the surgeon to explore further and look for other unanticipated pathologies. We present a case, clinically diagnosed as acute appendicitis and intraoperatively found to be an ulcerated ileal GIST. Case Presentation. A 28-year-old female without previous comorbidities presented to the emergency unit with sudden pain around the umbilicus that later migrated and localized to the RIF for one day. There was associated intermittent fever and anorexia without urinary symptoms. Abdominal examination revealed guarding and rebound tenderness at RIF. Examination by 2 senior surgeons at different points of time, the same day, made a clinical diagnosis of acute appendicitis. Ultrasonogram (USG) was inconclusive. At laparotomy through Lanz incision, the appendix was found to be normal and no other pathology was identified on walking bowel up to 3 ft proximal to ileocecal junction (ICJ). Just when closure was thought of, an ulcerated lesion could be seen through the medial aspect of the incision. On further exploration, a 7 × 5 cm ulcerated lesion arising from the antimesenteric border of the ileum was noted with localized interloop hemoperitoneum and inflammatory exudates. Ileal segmental resection anastomosis was done with peritoneal toileting. The lesion was subsequently reported to be an ulcerated malignant GIST. Conclusion. The commonest cause of RIF pain with localized peritonitis is an acutely inflamed appendix. Dilemma arises when the appendix is found to look normal. Further exploration is indicted to not miss other findings.